Pengaruh Pemasaran Internal dan Kualitas Layanan Internal Terhadap Kepuasan Pelanggan Internal (Studi Pada Industri Kepariwisataan di Daerah Istimewa Yogyakarta) - Jumadi Jumadi (Jurnal Ekonomi dan Bisnis, 2014)
The aim of this research is to investigate the implication of internal marketing and internal service quality effectivity towards internal customer satisfaction in Tourism Industry in Yogyakarta Special Territory. This internal marketing studyinvolves variables of motivation and reward system, effective communication, effective employee's selection, effective recruitment, effective development, effective support system, and healthy work environment. While the internal quality service aspects that will be examined in this study are: tangible, emphaty, responsiveness, reliability and assurance, and then their influences on internal customer satisfaction would be analyzed.The sample size is 210 respondents,which is determined using purposive sampling method. The main instrument for data collection in this study is through questionnaire. The analysis tool used to examine the hypothesis of the study is Structural Equation Modeling using AMOS Version 20.0 Software. The result of the study shows that: Internal marketing and internal quality service significantly influence internal customers satisfation. However, the internal quality service influence the internal customers satisfaction more significantly. Therefore the managers in tourism industry should improve the internal marketing more than the internal quality service.